The silent suffering women--a population based study on the association between reported symptoms and past and present infections of the lower genital tract. Issue 3 (June 1995) - Jonsson, M; Karlsson, R; Rylander, E; Bodén, E; Edlund, K; Evander, M; Gustavsson, A; Wadell, G
Abstract : OBJECTIVES--To assess the prevalence of lower genital tract symptoms and the association between reported symptoms and past and present signs of sexually transmitted diseases (STD) in young women. DESIGN--All women belonging to the 19-, 21-, 23- and 25-year age cohorts and living in the catchment area of the community health centre, were invited by mail to take part in a population-based study. The participants answered a structured questionnaire and a gynaecologic examination was performed. Samples for wet smear, cervical Pap smear, HPV DNA determination and Chlamydia trachomatis culture were taken at the gynaecologic examination. The presence of genital warts was noted. A blood sample was analysed for antibodies against C trachomatis and HSV-2. SETTING--The community health care centre was located in Umeå, a city in Northern Sweden. RESULTS--Of the 886 women who were eligible, 611 (70%) participated in the investigation. One out of four women reported symptoms from the lower genital tract. The most commonly reported symptoms were itching, followed by discharge, and soreness. The most commonly reported STD was C trachomatis (15%). The most prevalent present STD was HPV infection (20%) whereas C trachomatis infection could be isolated from 2.7% of the women. Antibodies against C trachomatis and HSV-2 were present among 22% and 6% of the women, respectively. There was a significant correlation between the women's complaint of vaginal discharge and previous C trachomatis infection, lack of lactobacilli and presence of leucocytosis in wet smear. CONCLUSIONS--We have in a population-based study of young healthy women found that one out of four women had some kind of lower genital tract complaint. Itching was the most commonly reported symptom and was associated with pseudohyphae and acetowhite patches. Reported vaginal discharge and soreness were associated with the history of a past C trachomatis infection and signs of a disturbed vaginal flora.